ANALISIS STRUKTUR KRISTAL BARIUM HEKSAFERRIT TIPE-W (Ba,Sr)CoTiFe16O27 - Tsaniya Mukarromah; Widyaningrum Indrasari; Erfan Handoko (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
W-type Barium Hexaferrite (BaMe2Fe12O27) has high value of currie temperature, very small coercivity (Hc), and the highest magnetic saturation (Ms) than the other ferrite materials. The W-type Barium Hexaferrite has a crystal structure that built up as a superposition of S and R blocks. Appearance of divalent and trivalent cations that distributed among various sublattices makes W-type Barium Hexaferrite become very interesting for basic studies and different applications. Synthesis and characterization of materials W-type Barium Hexaferrite by modify the value of Ba and Sr in Ba1-xSrxCoTiFe16O27 with composition x=0 and x=0.1 to determine the characteristics of the phases/crystals that formed, conducted through the process of smoothing powders of basic materials BaCO3, Fe2O3, SrCO3, Co3O4 and TiO2 by the High Energy Ball Mill for 1 hour in a wet condition (toluene). Phase forming in sintering 1100°C for 3 hours. By crystallographic analysis with measurements of X-Ray Diffractometer (XRD) on a target of Cobalt anode or anode Co, obtained phase analysis by qualitative and quantitative. From this result obtained magnetic materials BaCoTiFe16O27 and Ba0.9Sr0.1CoTiFe16O27. Lattice parameter values for BaCoTiFe16O27 and Ba0.9Sr0.1CoTiFe16O27 are a=b=5.89 Å, c= 23.24 Å dan a=b=5.89 Å, c= 23.23 Å. BaCoTiFe16O27 has a higher cell volume than Ba0.9S0.1CoTiFe16O27. Changes in cell volume affects the value of unisotropi crystal. Keywords: W-type Barium Hexaferrite, High Energy Ball Mill, X-Ray Diffractometer (XRD), Crystal Phase.